Snapshot of Social Work in China: Outcomes of Stakeholder Competition. (26th December 2020) - Yi-Bing, Xu; Quan-Cai, Li; Meng, Cui
Abstract: Since its introduction from the West, social work has unprecedentedly developed in China in recent decades. Accordingly, existing definitions of social work became outdated quickly inevitably. Indigenisation offers a useful perspective for understanding the development of social work in the rapidly changing context of China. However, indigenisation is often regarded as a linear and unidirectional process of knowledge transfer and adoption from the West to third world countries, which easily results in local dynamics getting ignored. This article views indigenisation as the result of competition amongst different local stakeholders. By discussing social work in China presently and examining the performance of different stakeholders, we argue that Chinese social work differs from social work in the West to some extent, especially in terms of its professional value, which has been challenged. Finally, the article highlights the implications of China's experience with social work for the international community.